The Multi-source National Forest Inventory of Finland – methods and results 2005 - Tomppo, Erkki; Haakana, Markus; Katila, Matti; Mäkisara, Kai; Peräsaari, Jouni (Finnish Forest Research Institute, 2009)
This article presents the results of the Finnish multi-source forest inventory based on satellite images, digital map data and field data. The main purpose of the article is to make multi-source forest inventory results available for the foresters, and all the readers interested in forests and forest environment. The field data originates from the 10th Finnish National Forest Inventory from years 2004 and 2005 and the updated field data of the 9th National Forest Inventory (NFI9) from years 1996 2003. The basic features of the employed improved k-NN method are described, as well as the new updating method briefly. The data from the field sample from the NFI9 were updated to the mid of year 2005 identifying the major changes on the field plots with the help of satellite images. Tree level growth models were applied to the remained trees to add the volume increments between field measurement and 2005.The results are presented by forestry centres and within forestry centres by municipalities. The estimates are given, for example for land areas, areas of tree species dominance, age and development classes and often separately for forests available for wood supply. The mean volume and total volume estimates are given in many different ways: mean volumes by tree species and by timber assortments for forest land, poorly productive forest land and their combination and also for forests available for wood supply, as well as by age and development classes. The biomass estimates are given by tree species groups in young thinning stands in which first commercial thinning was proposed for the first 5-year-period, separately for stem and bark and branches and foliage. The biomass estimates of mature forests are presented separately for branches, foliage and stem residuals, and stumps and large roots by tree species groups. All biomass estimates are given separately for land available for wood supply. The presented results can be employed in calculating forest resource estimates also for regions larger than municipalities. The error sources for the estimates as well as the reliability of the estimates are briefly discussed in Section 3.4.3 and Chapter 5.
Keywords: geneettinen algoritmi; k:n lähimmän naapurin menetelmä; kasvumallit; monilähdeinventointi; muutostunnistus; pienalue-estimointi; satelliittikuvat; stratifiointi; tilastollinen kalibrointi; valtakunnan metsien inventointi; change detection; genetic algorithms; growth models; k-nearest neighbours; multi-source forest inventory; national forest inventory; satellite images; small-area estimation; statistical calibration; stratification